Governance Quality and the Sustainable Development Goals in ASEAN Countries - Nurhayati, Siti; Purwatiningsih (Institut Bisnis dan Informatika Kesatuan, 2025)
Amid growing concern over sustainable development, this study aims to examine the relationship between the quality of national governance and the achievement of the Sustainable Development Goals (SDG) in ASEAN countries. Governance quality is measured using the six dimensions of the worldwide governance indicators, namely voice and accountability, political stability, government effectiveness, regulatory quality, rule of law, and control of corruption. Sustainable Development Goals performance is assessed using the SDG Index. The study employs a quantitative approach by analyzing 900 observations from 10 ASEAN countries over the period 2015–2024, using panel data regression complemented with robustness checks. The findings indicate that several governance dimensions, particularly political stability, government effectiveness, rule of law, and control of corruption, have a significant relationship with SDG achievement. In contrast, voice and accountability and regulatory quality do not show significant effects. The robustness test reveals a change in significance for regulatory quality, suggesting that this variable is sensitive to model specifications. This research contributes to the literature on public governance and sustainable development, especially within the context of developing countries in Southeast Asia. Practically, the findings provide important implications for ASEAN governments to strengthen governance reforms to accelerate the attainment of the 2030 SDG agenda. Keywords: Quality of Governance, Sustainable Development Goals, SDGs, WGI, ASEAN